Is the Relationship Between Adolescent Social Isolation and Anxiety‐Like Behaviors Altered by Microglia Ablation in Female Long Evans Rats? - Matthew A. Blumberg; Ava Shipman; Lidia Olyha; Stephen C. Gironda; Jeffrey L. Weiner (Brain and Behavior)
ABSTRACT Objective Despite extensive, cross‐disciplinary research revealing a relationship between early life stress (ELS) and an increased risk for neuropsychiatric disorders, the underlying processes mediating this relationship are not fully understood. Further, the majority of preclinical studies investigating this relationship have not taken sex differences into consideration. A growing body of work suggests that microglia, resident immune cells of the brain, are impacted by ELS and contribute to some of the maladaptive behavioral phenotypes in adulthood. Here, we utilized an adolescent social isolation (aSI) model of ELS in female rats to test the role of microglia in mediating the effects of ELS on anxiety‐related behaviors. Methods The present study sought to determine whether microglia ablation during aSI could prevent anxiety‐like behaviors in female Long Evans rats. A colony‐stimulating factor 1 receptor (CSF1‐r) inhibitor, PLX3397, was provided in chow to ablate microglia at the start of the isolation period (postnatal day (P) 21–42). During the aSI period, animals performed a battery of behavioral assays including the open field test, elevated plus maze, and successive alleys test. Following completion of the behavioral assays, brain tissue was collected to confirm the efficacy of PLX3397 and identify changes in microglia population density. Results Relative to group‐housed (GH) controls, aSI rats showed increased locomotor activity in the open field test and higher closed‐arm entries on the elevated plus maze. Although PLX3397 effectively ablated microglia across all animals, this treatment had minimal effects on observed aSI‐associated phenotypes. Conclusions Together, these data suggest that microglia are not required for behavioral adaptations promoted by aSI. Future studies will be needed to assess the role of microglia in the relationship between ELS and maladaptive behavioral phenotypes.